A New Persistent Photon-Gated Spectral Hole-Burning System: Zinc Tetraphenylporphyrin Linked to Polyvinylbenzylchloride-Co-Polystyrene. Issue 4 (1996) - Salhi, S.; Kulikov, S.; Bied-Charreton, C.; Galaup, J. P.
Abstract : Two colour photon-gated persistent spectral hole-burning via donor-acceptor electron transfer is reported in systems where the donor: zinc tetraphenylporphyrin (ZnTPP) and the acceptor: vinylbenzylchloride where linked to a polystyrene chain. A spectral hole is observed when the sample is irradiated using a gating light in addition to the wavelength-selective light. No effect of the gating light has been observed for ZnTPP dispersed in polystyrene (PS) even with efficient acceptors. In contrast, the efficiency of hole formation under two colour excitation is four times larger than that under one colour excitation in ZnTPP-PBCS/PMMA and nearly two times larger in ZnTPP-PBCS/PS.